Evaluating the Usefulness of a PNT Solution Using DGNSS-SBAS for Canoe Slalom: Simulated and Real-World Analysis - Macdermid PW; Irwin ME; Cochrane D (MDPI (Basel, Switzerland), 2024)
Featured Application: dGNSS-SBAS combined with geographical mapping software and georeferenced drone imagery is a cutting-edge approach to geographically track activities pertaining to canoe slalom. The PNT solution provided <0.3 m accuracy and provided a reliable means of tracking athletes’ trajectory, which could be used to monitor or develop best practice in athlete trajectories. This study investigated the accuracy and precision of a commercially available PNT solution that uses DGNSS-SBAS technology. Time and position data were sampled at a frequency of 20Hz during both a short and long trajectory of a simulated controlled dry-land slalom, as well as during a real-world on-water slalom exercise. The primary objective was to assess the positional accuracy, availability, integrity, and service continuity of the PNT solution while evaluating its ability to differentiate between trajectories. Additionally, the simulated results were compared with an on-water real-world slalom test to validate the findings. The results of the controlled dry-land slalom test indicate that the PNT solution provided accurate measurements with an overall mean ± SD Hrms of 0.20 ± 0.02 m. The integrity measures, HDOD and PDOP, were found to be ideal to excellent, with values of 0.68 ± 0.03 and 1.36 ± 0.07, respectively. The PNT solution utilised an average of 20 ± 1 satellites from the constellation, resulting in an accuracy of <1.5% when measuring the known trajectory of 50 simulated slalom runs. The data from the real-world on-water slalom test supported these findings, providing similar or improved results. Based on these findings, a PNT solution using DGNSS-SBAS can be considered an effective means of tracking athlete trajectory in the sport of canoe slalom. Future research should be conducted to quantify its efficacy more precisely.